ECONOMETARY ANALYSIS OF FACTORS AFFECTING THE PRACTICE OF PROVIDING MICRO-FINANCIAL SERVICES TO AGRICULTURAL PRODUCERS - Choriyevna, Murodova Dilnoza; Chori qizi, Murodova Mohigul; Shuxratovna , Abdiyeva Nargiza (International Journal of Psychosocial Rehabilitation, 2020)
The article provides an analysis of the factors affecting the provision of microfinance services to agricultural producers, as well as the results of the analysis of Agrobank operating in Uzbekistan.